PENDIDIKAN POLITIK INKLUSIF BAGI KOMUNITAS KAMPUNG NELAYAN MAJU DALAM MENINGKATKAN PARTISIPASI DEMOKRATIS DI SAMARINDA - Mulka, Sry Reski; Pratama, M. Aviv Adhitya Putra; Amalia, Dea Rizky; Hastira, Muh Fichriyadi; Damaianti, Alfiana Eka (An-Nizam, 2025)
This community service program was implemented in Rawa Makmur Village, Samarinda City, with a focus on improving political literacy and strengthening the social capacity of the fishing community. The activities used participatory methods through socialization, political literacy training, digital literacy, and community leadership combined with interactive lectures and group discussions. The program was held on September 11, 2025, and was attended by 50 participants from five fishing groups. The pre-test results showed that residents had a low understanding of democratic principles, the function of elections, and political rights, while the post-test results showed a significant improvement in these aspects. In addition, the active involvement of women and youth groups in the discussions marked the expansion of more inclusive political participation. Learning media in the form of printed modules, short videos, and community forums proved effective in facilitating the education process. This activity not only increased residents' political knowledge but also encouraged the creation of communication forums among fishermen as a platform for public policy advocacy. Thus, this program shows that community-based political education can be an effective strategy for strengthening participatory and sustainable local democracy.